2011
DOI: 10.1519/jsc.0b013e3181e501c1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Peripheral Muscle Structure and Function in Patients With Chronic Obstructive Pulmonary Disease With Different Nutritional Status

Abstract: The purpose of this study was to investigate the relationships between peripheral muscle structure (mass) and function (strength, endurance, and maximal aerobic capacity) in patients with chronic obstructive pulmonary disease (COPD) with different nutritional states. Thirty-nine patients (31 male) with moderate-severe COPD (63.5 ± 7.3 [SD] years) and 17 controls (14 male; 64.7 ± 5.5 [SD] years) underwent isokinetic (peak torque [PT]), isometric (isometric torque [IT]), and endurance strength (total work [TW]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
3
17
0
2
Order By: Relevance
“…On the other hand, our results meet the findings of those in the studies, that states that the muscular strength of the upper limbs of COPD patients can be preserved in the distal muscles, due to the fact that they are used in the daily activities, and reduced in the proximal muscles due to increased dyspnea during the activity sustained by the arm (18,19,20). However, studies highlight that there is a very strong correlation between the HGS and the strength of the other peripheral muscles, like the ones evaluated by the strength of the flexors of the elbow and the knee, as well as the respiratory muscle strength (maximal inspiratory muscle pressure and maximum voluntary ventilation) (15,21).…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, our results meet the findings of those in the studies, that states that the muscular strength of the upper limbs of COPD patients can be preserved in the distal muscles, due to the fact that they are used in the daily activities, and reduced in the proximal muscles due to increased dyspnea during the activity sustained by the arm (18,19,20). However, studies highlight that there is a very strong correlation between the HGS and the strength of the other peripheral muscles, like the ones evaluated by the strength of the flexors of the elbow and the knee, as well as the respiratory muscle strength (maximal inspiratory muscle pressure and maximum voluntary ventilation) (15,21).…”
Section: Resultssupporting
confidence: 91%
“…The reduced contractile ef iciency could be justi ied by this lower lean mass, especially given the strong correlation observed in this study, (Fig 3) and the indings obtained in other studies conducted by this laboratory, in which strong correlations were observed between muscle mass of the lower limb with peak torque, isometric force and total work in patients with COPD (25,26). However, this scenario was characterized by less muscle mass (agent) and lower torque or generated work (product), which does not explain the increased O 2 extraction observed in this study (constant of proportionality: extraction O 2 ∝ agent ‹=› product).…”
Section: Low Muscular Capacitysupporting
confidence: 77%
“…ASMI positively contributed to muscle strength, peak workload and CET (CET only in men), whereas A/G%FM positively contributed to muscle strength and 6MWD in men, but negatively to 6MWD in women. The better prediction of ASMI for muscle strength and peak workload as compared with CET and 6MWD can be attributed to the direct interaction between muscle mass and weakness in this population, whereas muscle endurance is suggested to be affected by multiple additional factors related to COPD [35]. Noticeable is the independent contribution of BMC to endurance in the regression model.…”
Section: Discussionmentioning
confidence: 84%